Introduction. Toussaint en Italie, l’Italie chez Toussaint - Margareth Amatulli; Christophe Meurée (MediAzioni)
Italy is ubiquitous in Jean-Philippe Toussaint's work, since almost all his books have been translated, and some have even been retranslated. Among contemporary French-speaking authors, Toussaint is undoubtedly the one who has explored the Italian peninsula most extensively: his familiarity with the country's landscapes, culture, and even language is evident in every aspect of his multi-modal work (narratives, films, photography, art installations, performances). This special issue represents a step that will perhaps lead our author to explore Italy in a different way, constantly reinventing it and adding new facets to it.